2012
DOI: 10.1007/s11274-012-1042-1
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol lacks antifungal activity against Candida albicans

Abstract: The putative candicidal activity of resveratrol is currently a matter of controversy. Here, the antifungal activity as well as the antioxidant response of resveratrol against Candida albicans, have been tested in a set of strains with a well-established genetic background At the doses usually employed in antifungal tests (10-40 μg/ml), resveratrol has no effect on the exponential growth of the C. albicans CAI.4 strain, a tenfold increase (400 μg/ml) was required in order to record a certain degree of cell kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…In fact, a study indicates that resveratrol is not effective against both C. albicans and non- C. albicans species [ 101 ]. In another study, resveratrol antifungal activity against C. albicans could be reached at 400 μg/mL, thereby minimizing the antifungal role of resveratrol against C. albicans -caused infections [ 103 ].…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…In fact, a study indicates that resveratrol is not effective against both C. albicans and non- C. albicans species [ 101 ]. In another study, resveratrol antifungal activity against C. albicans could be reached at 400 μg/mL, thereby minimizing the antifungal role of resveratrol against C. albicans -caused infections [ 103 ].…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…The effect of resveratrol (3,5,4-trihydroxystilbene), a close analogue of PTE, on C. albicans has been investigated previously (57)(58)(59). However, its antifungal effect was much weaker than PTE.…”
Section: Met14mentioning
confidence: 99%
“…Previously, Collado-González et al suggested that resveratrol did not possess critical antifungal and killing effects against C. albicans even in high concentration [8]. However, in this study, we focused on the intracellular mechanism of resveratrol in C. albicans.…”
Section: Resveratrol Induces Apoptosis Through the Caspasedependent Pmentioning
confidence: 81%